A 10-Year Review of the Management of Ocular Mucous Membrane Pemphigoid: A Private Practice Experience. Issue 5 (13th May 2023) - Johnson, Kasey B.; Rosenbaum, James T.; Yarter, Jason T.; Broadbent, Talmage; Michels, Kevin S.
Abstract : Purpose: Ocular mucous membrane pemphigoid (OcMMP) is a rare and potentially blinding condition for which consensus treatment guidelines do not exist. The purpose of this study was to assess the effectiveness and safety of various immunomodulatory agents in the treatment of OcMMP in a private practice setting. Methods: We conducted a 10-year retrospective chart review of patients managed with OcMMP (n = 22). The median age at diagnosis was 73 (range: 35–91) years, and 59% (13/22) of patients were female. Visual acuity, Foster stage, and adverse effects (AEs) were documented. Treatment outcomes for each treatment episode were qualified at 3 months as complete response (CR), response (R), or failure (F). After 3 months, CR was then further subqualified as sustained CR, reactivation after initial CR, or AE after initial CR. The Fisher exact test P values were calculated for each outcome in comparison with mycophenolate. Results: Twenty patients were treated with an immunomodulatory agent for a total of 55 treatment episodes. In comparison to dapsone, mycophenolate was more likely to achieve sustained CR (50% vs. 0%, P = 0.022) and R (100% vs. 50%, P = 0.007), and less likely to fail (0% vs. 50%, P = 0.007). Dapsone was also more likely to be discontinued because of AEs than mycophenolate (40% vs. 6%, P = 0.041). Conclusions: Mycophenolate is a superior first-line agent to dapsone in the treatment of OcMMP. Although not statistically significant, mycophenolate trends toward superiority over methotrexate as well. Mycophenolate is very effective when used in combination with rituximab. Azathioprine remains a reasonable second-line agent.